Lithium supplement material, positive pole piece and lithium ion battery
By using lithium sulfite, lithium phosphite and other lithium supplement additives to form hydrogen bonds with polymatrionic acid in lithium ion batteries, the problem of irreversible consumption of lithium ions and excessive lithium supplement potential in lithium ion batteries is solved, and the problem of excessive lithium supplement potential in lithium ion batteries is achieved. The uniform release of lithium ions and the improvement of battery performance.
Patent Information
- Application Number
- CN202411707895.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
AI Technical Summary
During the charging process, the existing lithium-ion batteries irreversibly consume lithium ions due to the generation of SEI film, resulting in low Coulomb efficiency for the first time, affecting the battery capacity and energy density. In addition, the lithium-ion potential of the existing lithium-ion supplement material can easily lead to metal ions. Dissolution affects battery performance.
Colloidal materials containing lithium sulfite, lithium phosphite and lithium oxalate are used as lithium supplement additives. By forming hydrogen bonds with polymatriate, lithium ions are uniformly distributed, the lithium supplement potential is reduced, and uniformly dissolved in the positive electrode sheet. , avoid metal ions dissolution.
The uniform release of lithium ions in lithium-ion batteries is achieved, the lithium supplement potential is reduced, the first Coulomb efficiency and battery performance of lithium-ion batteries are improved, the dissolution of metal ions is avoided, and the stability and energy density of the battery are enhanced.
Smart Images

Figure BDA0005154951490000071 
Figure BDA0005154951490000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and relates to a lithium supplement material, a positive electrode sheet and a lithium ion battery. Background Art
[0002] During the first charging process of a lithium-ion battery, the organic electrolyte will undergo a reduction and decomposition reaction on the surface of the negative electrode such as graphite to form a dense solid electrolyte interface (SEI) film; the SEI film is located between the metal negative electrode and the electrolyte, and is crucial to the long-term stability of the battery; but the formation of the SEI film irreversibly consumes a large amount of lithium from the positive electrode, which can easily cause the first coulombic efficiency of the battery cycle to be low, thereby reducing the capacity and energy density of the lithium-ion battery; in order to offset the irreversible lithium loss in this process and improve battery performance, lithium ions are replenished into the lithium-ion battery before it works. This lithium replenishment step is also called "pre-lithiation", which replenishes the electrode material with lithium through pre-lithiation.
[0003] The positive electrode lithium replenishment is usually done by electrochemical method. By adding lithium replenishment materials to the positive electrode of the lithium-ion battery, the lithium replenishment materials will decompose and release active lithium during the charging process of the battery to make up for the irreversible active lithium loss caused by the growth of the SEI film. The existing technology generally adds sacrificial lithium salts or lithium-rich additives directly to the positive electrode formula. Commonly used positive electrode lithium replenishers can be mainly divided into the following three categories:
[0004] The first category is binary lithium-containing compounds, such as Li2O, Li2O2, Li3N, Li2S, etc., which are usually carbon-coated on the surface or used with metal nanoparticles to catalyze the active release of lithium ions from lithium-supplementing materials;
[0005] The second category is lithium-rich compounds, such as lithium-rich lithium iron oxide (Li5FeO4), lithium nickel oxide (Li2NiO2), etc.
[0006] The third category is lithium complexes, such as Li2S / Co, LiF / Co, Li2O / Co, etc.;
[0007] When replenishing lithium, the lithium replenishing material needs to have a certain redox potential to participate in the chemical reaction. At the same time, lithium ions also need a certain potential to be released from the crystal particles of these lithium replenishing materials. Therefore, the lithium replenishing potential of the lithium replenishing agent must not only include the theoretical redox potential, but also the potential for lithium ions to escape from the crystal. However, when the lithium replenishing potential is too high, it is easy to cause the dissolution of metal ions in the lithium replenishing material, affecting the battery performance. Summary of the invention
[0008] In view of the above problems existing in the prior art, the object of the present invention is to provide a lithium supplement material, a positive electrode sheet and a lithium ion battery.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] The present invention provides a lithium supplement material, comprising a colloidal material and a lithium supplement additive dissolved in the colloidal material; the mass percentage of carboxyl groups in the colloidal material is a%, the mass percentage of the lithium supplement additive in the lithium supplement material is b%, and a / b≥1.3;
[0011] The lithium supplement additive includes at least one of lithium sulfite, lithium phosphite and lithium oxalate.
[0012] In some embodiments, the value of a / b is 1.3≤a / b≤6.
[0013] In some embodiments, the colloid material includes polymaleic acid, and / or the molecular weight of the polymaleic acid is 500,000 to 1.5 million.
[0014] The present invention also provides a positive electrode plate, comprising a current collector and a membrane layer arranged on at least one side surface of the current collector; the membrane layer comprises the lithium supplement material as described above.
[0015] In some embodiments, the membrane layer further comprises a sodium supplement additive.
[0016] In some embodiments, the sodium supplement additive includes at least one of sodium sulfite, sodium phosphite and sodium oxalate, and / or the content of the sodium supplement additive in the membrane layer is less than the content of the lithium supplement additive in the membrane layer.
[0017] In some embodiments, the membrane layer further includes a positive electrode active material, a binder, and a conductive agent.
[0018] In some embodiments, the mass ratio of the colloid material to the binder is (1-4):(0.2-1.5).
[0019] In some embodiments, the binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, and polytetrafluoroethylene; and / or, based on 100 parts by weight of the diaphragm layer, the content of the binder in the diaphragm layer is 0.2 to 1.5 parts; and / or, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, carbon fiber, and conductive graphite.
[0020] The present invention further provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The lithium supplement additive in the present invention comprises lithium sulfite, lithium phosphite and lithium oxalate, and the colloidal material for dissolving the lithium supplement additive contains polybutenedioic acid; polybutenedioic acid contains a large number of carboxyl groups, and sulfite and oxalate can combine with the carboxyl groups to generate hydrogen bonds, so that lithium sulfite and lithium oxalate can be evenly distributed in the colloidal material containing polybutenedioic acid; when the lithium supplement additive is dissolved in the slurry, lithium ions can be directly released from the slurry layer on the pole piece without being released from the crystal particles, and the theoretical lithium supplement potential does not need to be calculated into the release potential of the lithium ions; therefore, the theoretical lithium supplement potential of the lithium supplement additive in the present invention is relatively low, and lithium can be supplemented in the formation stage; in the lithium supplement material obtained by the present invention, the lithium supplement additive is evenly dissolved in the colloidal material, the lithium supplement amount is high, and no metal is dissolved in the lithium supplement process. DETAILED DESCRIPTION
[0023] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0024] The present invention provides a lithium supplement material, a colloidal material and a lithium supplement additive dissolved in the colloidal material; the mass percentage of carboxyl groups in the colloidal material is a%, the mass percentage of the lithium supplement additive in the lithium supplement material is b%, and a / b≥1.3;
[0025] The lithium supplement additive includes at least one of lithium sulfite, lithium phosphite and lithium oxalate.
[0026] Preferably, the value of a / b is 1.3≤a / b≤6; the content of carboxyl groups in the colloidal material and the amount of the lithium supplement additive in the lithium supplement material are controlled to ensure that the lithium supplement additive can be uniformly dispersed and dissolved in the colloidal material.
[0027] Preferably, the colloid material comprises polymaleic acid, and / or the molecular weight of the polymaleic acid is 500,000 to 1.5 million.
[0028] The lithium supplement additive in this scheme is insoluble in common positive electrode slurry solvents such as N-methylpyrrolidone (NMP), which means that under normal circumstances, if the lithium supplement additive in this scheme, such as lithium sulfite or lithium oxalate, is directly added to the positive electrode slurry, they will be dispersed in the slurry in the form of crystal particles; however, the colloidal material used in this scheme contains polymaleic acid, which contains a large number of carboxyl groups. The lithium supplement additive in this scheme, such as lithium phosphite, can form a stable hydrogen bond network with the carboxyl group in the lithium supplement additive, such as lithium phosphite. The same is true for lithium phosphite and lithium oxalate; when these lithium supplement additives are dissolved in the colloidal material, lithium ions can be directly released from the slurry layer on the electrode without being released from the crystal particles, and the lithium ion release potential does not need to be added when calculating the theoretical lithium supplement potential; therefore, this scheme can reduce the theoretical lithium supplement potential of the lithium supplement additive, so that the lithium supplement additive can supplement lithium in the formation stage of the lithium ion battery. The lithium supplement material obtained by the invention is not doped with crystal particles, the lithium supplement additive is uniformly dissolved in the slurry, the lithium supplement amount is high and no metal is dissolved during the lithium supplement process.
[0029] The present invention also provides a positive electrode plate, comprising a current collector and a membrane layer arranged on at least one side surface of the current collector; the membrane layer comprises the above-mentioned lithium supplement material.
[0030] Furthermore, the membrane layer also includes a sodium supplement additive.
[0031] Furthermore, the sodium supplement additive includes at least one of sodium sulfite, sodium phosphite and sodium oxalate, and / or the content of the sodium supplement additive in the membrane layer is less than the content of the lithium supplement additive in the membrane layer; sodium and lithium are elements of the same family and have similar chemical properties; by adding sodium to the lithium ion battery, the performance of the lithium ion battery can be improved to a certain extent; similarly, the sodium supplement additive can also be dispersed and dissolved in the positive electrode slurry through polybutenedioic acid, and the released sodium ions can help increase the stability of the SEI film in the lithium ion battery; without affecting the operation of the lithium ion battery and achieving the expected lithium supplement effect, the amount of the sodium supplement additive needs to be strictly controlled so that it does not exceed the amount of the lithium supplement additive.
[0032] Furthermore, the membrane layer also includes a positive electrode active material, a binder and a conductive agent.
[0033] Furthermore, the mass ratio of the colloid material to the binder is (1-4):(0.2-1.5).
[0034] Furthermore, the binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, and polytetrafluoroethylene; and / or, based on 100 parts by weight of the diaphragm layer, the content of the binder in the diaphragm layer is 0.2 to 1.5 parts; and / or, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, carbon fiber, and conductive graphite; the binder and conductive agent in the present invention include but are not limited to the above-mentioned compounds.
[0035] Experimental Group 1
[0036] Provided are a lithium supplement material, a positive electrode sheet and a lithium ion battery, the preparation steps of which are as follows:
[0037] 1. Preparation of lithium supplement materials
[0038] Adding lithium supplement additive Li2SO3 to the colloidal material polymaleic acid, stirring and dissolving, to obtain a lithium supplement material;
[0039] The mass percentage a% of the carboxyl group in the colloid material is 77.57%, the mass percentage b% of the lithium supplement additive in the lithium supplement material is 77.57%, a / b=1, and the molecular weight of the polymaleic acid is 800,000;
[0040] 2. Preparation of positive electrode
[0041] Add NMP and a binder to the obtained lithium supplement material and stir evenly; then add a conductive agent and stir evenly; add 1 / 2 amount of positive electrode active material and stir evenly; then add the remaining positive electrode active material and stir evenly to obtain a positive electrode slurry; use a coating machine to coat the obtained positive electrode slurry on the surface of an aluminum foil, dry it, and roll it to form a film layer to obtain a positive electrode sheet;
[0042] In the positive electrode slurry, the positive electrode active material is lithium cobalt oxide, the binder is polyvinylidene fluoride (PVDF), and the conductive agent is conductive carbon black (SP);
[0043] The components are used in the following amounts by weight: 89.08 parts of lithium cobalt oxide, 0.5 parts of PVDF, 8.92 parts of lithium supplement additive Li2SO3, 1.5 parts of SP, and the mass ratio of the colloidal material polymaleic acid to the binder PVDF is 2:0.5.
[0044] 3. Preparation of lithium-ion batteries
[0045] The negative electrode sheet, the separator and the obtained positive electrode sheet are assembled into a battery assembly, and the electrolyte is injected, and the lithium-ion battery is obtained after formation, packaging and capacity division.
[0046] Experimental Group 2
[0047] Provided are a lithium supplement material, a positive electrode sheet and a lithium ion battery, which differ from experimental group 1 only in that: the content b% of the lithium supplement additive in the lithium supplement material is 59.67%, a / b=1.3; in the preparation of the positive electrode sheet, the components are used in the following amounts by weight: 93.04 parts of lithium cobalt oxide, 0.5 parts of PVDF, 4.96 parts of the lithium supplement additive and 1.5 parts of SP; the remaining steps are the same as those of experimental group 1.
[0048] Experimental Group 3
[0049] Provided are a lithium supplement material, a positive electrode sheet and a lithium ion battery, which differ from experimental group 1 only in that: the content b% of the lithium supplement additive in the lithium supplement material is 38.79%, a / b=2; in the preparation of the positive electrode sheet, the components are used in the following amounts by weight: 94.73 parts of lithium cobalt oxide, 0.5 parts of PVDF, 3.27 parts of the lithium supplement additive and 1.5 parts of SP; the remaining steps are the same as those of experimental group 1.
[0050] Experimental Group 4
[0051] Provided are a lithium supplement material, a positive electrode sheet and a lithium ion battery, which differ from experimental group 1 only in that: the content b% of the lithium supplement additive in the lithium supplement material is 19.4%, a / b=4; in the preparation of the positive electrode sheet, the components are used in the following amounts by weight: 95.52 parts of lithium cobalt oxide, 0.5 parts of PVDF, 2.48 parts of the lithium supplement additive and 1.5 parts of SP; the remaining steps are the same as those of experimental group 1.
[0052] Experimental Group 5
[0053] Provided are a lithium supplement material, a positive electrode sheet and a lithium ion battery, which differ from experimental group 1 only in that: the content b% of the lithium supplement additive in the lithium supplement material is 12.93%, a / b=6; in the preparation of the positive electrode sheet, the components are used in the following amounts by weight: 95.7 parts of lithium cobalt oxide, 0.5 parts of PVDF, 2.3 parts of the lithium supplement additive and 1.5 parts of SP, and the remaining steps are the same as those of experimental group 1.
[0054] Experimental Group 6
[0055] Provided are a lithium supplement material, a positive electrode sheet and a lithium ion battery, which differ from experimental group 1 only in that: the content b% of the lithium supplement additive in the lithium supplement material is 11.08%, a / b=7; in the preparation of the positive electrode sheet, the components are used in the following amounts by weight: 95.75 parts of lithium cobalt oxide, 0.5 parts of PVDF, 2.25 parts of the lithium supplement additive and 1.5 parts of SP, and the remaining steps are the same as those of experimental group 1.
[0056] Test Group 7
[0057] Provided are a lithium supplement material, a positive electrode plate and a lithium ion battery, which differ from experimental group 1 only in that: the lithium supplement additive is Li2HPO3, the content b% of the lithium supplement additive in the lithium supplement material is 59.67%, and a / b=1.3; in the preparation of the positive electrode plate, the components are used in the following amounts by weight: 93.04 parts of lithium cobalt oxide, 0.5 parts of PVDF, 4.96 parts of the lithium supplement additive and 1.5 parts of SP, and the remaining steps are the same as those of experimental group 1.
[0058] Experimental Group 8
[0059] Provided are a lithium supplement material, a positive electrode plate and a lithium ion battery, which differ from experimental group 1 only in that: the lithium supplement additive is Li2C2O4, the content b% of the lithium supplement additive in the lithium supplement material is 59.67%, and a / b=1.3; in the preparation of the positive electrode plate, the components are used in the following amounts by weight: 93.04 parts of lithium cobalt oxide, 0.5 parts of PVDF, 4.96 parts of the lithium supplement additive and 1.5 parts of SP, and the remaining steps are the same as those of experimental group 1.
[0060] Experimental Group 9
[0061] Provided are a lithium supplement material, a positive electrode plate and a lithium ion battery, which differ from experimental group 1 only in that: the content b% of the lithium supplement additive Li2SO3 in the lithium supplement material is 50.05%, a / b=1.55; in the preparation of the positive electrode plate, the components used are as follows, by weight: 93.04 parts of lithium cobalt oxide, 0.5 parts of PVDF, 3.96 parts of lithium supplement additive, 1 part of sodium supplement additive Na2SO3 and 1.5 parts of SP, and the remaining steps are the same as those of experimental group 1.
[0062] Preparation of positive electrode sheet: add sodium supplement additive, NMP and binder to the obtained lithium supplement material, stir evenly; then add conductive agent, stir evenly; add 1 / 2 amount of positive electrode active material, stir evenly; then add the remaining positive electrode active material, stir evenly to obtain positive electrode slurry; use a coating machine to apply the obtained positive electrode slurry on the surface of aluminum foil, dry, roll and press to form a positive electrode film layer to obtain a positive electrode sheet.
[0063] Test group 10
[0064] Provided are a lithium supplement material, a positive electrode plate and a lithium ion battery, which differ from Experimental Group 2 only in that the positive electrode active material used in Experimental Group 10 is a nickel-cobalt-manganese ternary material (NCM811).
[0065] Experimental Group 11
[0066] A lithium supplement material, a positive electrode plate and a lithium ion battery are provided, which differ from the experimental group 2 only in that the positive electrode active material used in the experimental group 11 is lithium iron phosphate (LFP).
[0067] Test Group 12
[0068] Provided are a lithium replenishing material, a positive electrode sheet and a lithium ion battery, which differ from Experimental Group 2 only in that: a lithium replenishing additive Li2SO3 is directly added to the positive electrode slurry. Specifically, in the preparation of the positive electrode sheet, the components used are as follows, by weight: 93.04 parts of lithium cobalt oxide, 2.5 parts of PVDF, 1.5 parts of SP and 2.96 parts of Li2SO3, and the remaining steps are the same as Experimental Group 2.
[0069] Blank group 1
[0070] A positive electrode plate and a lithium-ion battery are provided, which differ from the experimental group 12 only in that: no lithium supplement additive Li2SO3 is added, and the component amounts are as follows: 96 parts of lithium cobalt oxide, 2.5 parts of PVDF and 1.5 parts of SP, and the remaining steps are the same as those of the experimental group 12.
[0071] Blank Group 2
[0072] Provided are a positive electrode plate and a lithium-ion battery, which differ from the blank group 1 only in that the positive electrode main material is a nickel-cobalt-manganese ternary material (NCM811), and the component amounts are as follows: 96 parts of the nickel-cobalt-manganese ternary material (NCM811), 2.5 parts of PVDF, and 1.5 parts of SP.
[0073] Blank group 3
[0074] Provided is a positive electrode plate and a lithium-ion battery, which differ from the blank group 1 only in that the main material of the positive electrode is lithium iron phosphate (LFP), and the component amounts are as follows: 96 parts of LFP, 2.5 parts of PVDF and 1.5 parts of SP.
[0075] Decomposition potential test of lithium supplement additives
[0076] The main material of the positive electrode is lithium cobalt oxide: at 25°C, the batteries of test groups 1-12 were charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V constant voltage and left for 5 minutes, and then charged to 4.5V at 0.1C constant current, and the voltage (V) and capacity (Q) data obtained in the recording device were recorded. The dQ / dV data was obtained through mathematical processing. The dQ / dV curve that changes with V can be obtained by plotting the voltage data V as the horizontal axis and the corresponding dQ / dV as the vertical axis. The voltage value corresponding to the peak position of the curve in the range of 3.65V-4.5V is the decomposition voltage (lithium replenishment potential) of the lithium replenishment additive.
[0077] Table 1. Test data of decomposition potential of lithium supplement additives in test groups 1-12
[0078]
[0079] Observe the data of test group 1 in Table 1. Since lithium sulfite in test group 1 is only partially dissolved, two lithium replenishing potentials appear, wherein lithium sulfite dissolved in polymaleic acid decomposes at 2.3 V, and undissolved lithium sulfite decomposes at 4.3 V. By observing the data in Table 1, it can be seen that compared with the lithium replenishing potential obtained by directly adding the lithium replenishing additive to the slurry in test group 12, the lithium replenishing potential obtained in test groups 1-11 is lower. It is easy to know that the present invention uses colloidal materials to dissolve the lithium replenishing additive and then adds it to the positive electrode, and when a / b≥1.3, the decomposition potential of the lithium replenishing additive can be significantly reduced.
[0080] Performance Testing
[0081] The lithium-ion batteries obtained from the blank groups 1-3 and the test groups 1-12 were subjected to cyclic charge and discharge tests at room temperature to obtain the cycle capacity retention rate, and the first coulombic efficiency and positive electrode active material utilization efficiency were calculated based on the first charge gram capacity and first discharge gram capacity obtained from the formation and capacity distribution data.
[0082] In Table 2, η1 is the first coulombic efficiency of the battery, that is, the ratio of the first discharge capacity of the battery to the first charge capacity. η2 is the utilization efficiency of the positive electrode active material of the battery, that is, the ratio of the first discharge capacity of the battery to the first charge capacity of the active material. The first charge capacity of the active material can be obtained by multiplying the mass of the active material in the battery by the material charge gram capacity. η1 is the conventional first efficiency of the battery, but the disadvantage is that after adding the positive electrode lithium replenishment additive, it cannot truly reflect the lithium replenishment effect of the lithium replenishment additive; η2 can make up for the above defects and can reflect the utilization efficiency of the positive electrode active material after lithium replenishment. When lithium replenishment is not performed, η1=η2.
[0083] Table 2. Performance test data of blank groups 1-3 and test groups 1-12
[0084]
[0085] Observing the data of blank group 1 and test groups 1-6 in Table 2, it can be seen that with the addition of lithium supplement additive Li2SO3, the first coulomb efficiency η1 of the battery decreases slowly at first (test groups 4-6), while the utilization efficiency η2 of the positive electrode active material increases rapidly. This is because the charging capacity and discharge capacity increase simultaneously when replenishing lithium, so η1 changes less; the increase in charging capacity comes from the lithium supplement additive, and the increase in discharge capacity is due to the entry of more lithium ions into the positive electrode active material, so η1 changes more. When the amount of lithium that the positive electrode active material can accommodate is close to the material limit, the discharge capacity changes little (test groups 2-3), and the charging capacity increases more, so η1 decreases rapidly and η2 increases less. When the lithium supplement additive is used excessively (test group 1), η1 is very low. At this time, the lithium supplement additive occupies a lot of the capacity of the active material, and more lithium is stored in the negative electrode without being released, which will reduce the battery capacity.
[0086] From the data of test group 7 and test group 8 in Tables 1 and 2, it can be seen that the lithium supplement additives Li2HPO3 and Li2C2O4 both have good lithium supplement effects.
[0087] From the data of test group 9 in Tables 1 and 2, it can be seen that after adding the sodium supplement additive, the cycle performance of the lithium-ion battery obtained is similar to that of adding the lithium supplement additive. This is because the oxidation potential of sulfite is low and it will decompose to form a SEI film before the positive electrode active material takes effect, and will not have a negative impact on the capacity of the positive electrode active material.
[0088] From the data of test group 10 and test group 11 in Tables 1 and 2, it can be seen that the lithium supplement additive in this scheme is also applicable to ternary and lithium iron phosphate positive electrode active materials.
[0089] From the data of test group 12 in Tables 1 and 2, it can be seen that when polymaleic acid is not added to the colloidal material, although a certain lithium replenishing effect can be achieved, the lithium replenishing effect is weaker than that of test groups 1-11; this further demonstrates the superiority of the present scheme of using polymaleic acid to dissolve the lithium replenishing additive, making it evenly dispersed in the colloidal material, and reducing the lithium replenishing potential of the lithium replenishing additive.
[0090] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A lithium supplement material, characterized in that: The invention comprises a colloidal material and a lithium supplement additive dissolved in the colloidal material; the mass percentage of carboxyl groups in the colloidal material is a%, the mass percentage of the lithium supplement additive in the lithium supplement material is b%, and a / b≥1.3; The lithium supplement additive includes at least one of lithium sulfite, lithium phosphite and lithium oxalate.
2. The lithium supplement material according to claim 1, characterized in that: The value of a / b is 1.3≤a / b≤6.
3. The lithium supplement material according to claim 1, characterized in that: The colloid material includes polymaleic acid, and / or the molecular weight of the polymaleic acid is 500,000 to 1.5 million.
4. A positive electrode sheet, characterized in that: It comprises a current collector and a membrane layer arranged on at least one side surface of the current collector; the membrane layer comprises the lithium supplement material as claimed in any one of claims 1 to 3.
5. The positive electrode sheet according to claim 4, characterized in that: The membrane layer also includes a sodium supplement additive.
6. The positive electrode sheet according to claim 5, characterized in that: The sodium supplement additive includes at least one of sodium sulfite, sodium phosphite and sodium oxalate, and / or the content of the sodium supplement additive in the membrane layer is less than the content of the lithium supplement additive in the membrane layer.
7. The positive electrode sheet according to claim 4, characterized in that: The membrane layer also includes a positive electrode active material, a binder and a conductive agent.
8. The positive electrode sheet according to claim 7, characterized in that: The mass ratio of the colloid material to the binder is (1-4):(0.2-1.5).
9. The positive electrode sheet according to claim 7, characterized in that: The binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, and polytetrafluoroethylene; and / or, based on 100 parts by weight of the diaphragm layer, the content of the binder in the diaphragm layer is 0.2 to 1.5 parts; and / or, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, carbon fiber, and conductive graphite.
10. A lithium ion battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 4 to 9.